Internal Audit Strategies in Strengthening Corporate Governance: A Risk Management and Compliance Analysis - Sumardi, Sumardi; Tiblola, Fredy Arios; Purwadi, Anto (International Journal of Management Science and Information Technology, 2026)
This study aims to analyze the role of internal audit in strengthening corporate governance. This study focuses on the risk management and compliance aspects of an organization's ability to comply with accepted standards, laws, and regulations, especially in this era of digital transformation. Internal audit plays a crucial role in reviewing the suitability of internal control systems, risk management, and compliance. The application of technology in internal audit has enabled increased risk detection efficiency while ensuring better compliance. This study uses a comparative approach, comparing companies that have switched to digital technology systems for internal audit with companies that still use traditional methods. Data collection comes from interviews, surveys, and document analysis of 200 respondents (internal auditors, audit committee members, and senior managers) in 50 companies. Newly introduced digital technologies in internal audit have been shown to strengthen risk management and compliance, thereby improving overall corporate governance. Organizations with strong governance structures, having more independent directors and more effective audit committees, tend to be more successful in risk management. The study also found that clear policies on internal control play a very important role in improving compliance. However, issues such as unreliable investment costs, complete system integration, and resistance from top management remain barriers to implementing digital technologies in internal audit.